Retrospective audit of the value of the pancreolauryl test in a district general hospital. Issue 934 (3rd September 2003) - Murray, I A; Clenton, S; McGeorge, B A; Safe, A F
Abstract : Objectives: To audit the specificity and value of the pancreolauryl test (PLT) for the diagnosis of pancreatic insufficiency. Design: A retrospective case note review of 47 patients who had a PLT during three consecutive years. Setting: A 650 bedded district general hospital. Main outcome measures: Patient demographics, symptoms, baseline blood, endoscopic and radiological investigations, and alcohol consumption were related to the results of the PLT to determine if the test could be better targeted. Response to therapy and final diagnoses were noted to determine the specificity of the test. Results: Forty seven patients had a PLT during the three years studied. All successfully performed the test as outpatients. Seven inconclusive tests were repeated. Thirty eight patients (81%) had diarrhoea, of whom 10 (21%) described steatorrhoea; 23 (49%) had an abnormal PLT. All with an abnormal test had diarrhoea, more frequently describing watery stools than steatorrhoea. Those treated with pancreatic enzyme supplements had an excellent response, although two of these had a final diagnosis of coeliac disease. Nineteen patients with an abnormal PLT were thought to be suffering from pancreatic insufficiency. All patients with a normal PLT were clinically thought not to have pancreatic insufficiency. Age, sex, and alcohol intake correlated poorly with final diagnosis. Conclusions: The PLT can be used in a district general hospital setting as an outpatient test for pancreatic insufficiency and has a specificity of 83%–91%. Its use should be restricted to thse presenting with diarrhoea, not necessarily steatorrhoea, and not restricted to those with a history of high alcohol consumption.